Relationship between institution status and the organizational culture of community health centres in Bali - Maria Magdalena Zulian Puji Astuti; Ni Made Sri Nopiyani; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: The adoption of an appropriate organizational culture model can be instrumental in ensuring the success of an institution. Currently, public health centres (PHCs) in Indonesia are being remodeled to function as independent units managed as regional public service agencies (BLUD). This study aims to determine whether there are differences in the organizational culture of BLUD PHCs with non BLUD PHCs. Methods: Survey was conducted with 142 staff from BLUD PHCs and with 109 staff from non BLUD PHCs, selected using stratified random sampling technique. Data were collected by completing the organizational culture assessment instrument (OCAI) according to the concept of Competing Values ​​Framework (CVF) and analyzed descriptively to determine aspects of the organizational culture. Results: Staff at the BLUD PHCs presented with lower education levels, were older and with an average longer working period compared to staff at the non BLUD PHCs. A hierarchical organizational culture was found in three BLUD PHCs and in one BLUD PHCs, while the other two non BLUD PHCs indicated a tendency towards a clan culture. It is hoped that in the next two years all PHC will adhere to a clan organizational culture model. Conclusions: Significant differences in age, education and number of working years between BLUD PHCs and non BLUD PHCs determine the organizational culture model adopted. The current adopted organizational culture is hierarchical whereas a transition to clan culture is desired.